Analisis Pengaruh Kredit Lembaga Keuangan Mikro Terhadap Perkembangan Usaha Industri Kecil di Kecamatan Mempura Kabupaten Siak Provinsi Riau - Yudhaprawira, Ryan; Rifai, Ahmad; ', Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research is to analyze the influences of micro credits financial institution (coperation and PT. Persi) to the development of small industry at Mempura Sub District, Siak Regency, Riau Province. The samples has conducted by using saturated sampling technique, amount of of samples are 31 small industries. The result of research obtained that small industries which earned credit is not better developed compared to small industries which not earned credit. It's showed by there’s no different of assets, sales turnover, number of employees, between small industries, except of working hours and the scope of the marketing of industries that have earned credit is greater than the industries does not get the credit. It is reinforced by the result of analysis of the logistics that showed there was no difference of assets, sales turnover, number of employees, number of hours worked in marketing coverage among small industries that earned credit and small industries that not earned credit. Key words : development, industries which received credit, industries which not received credit